Economic Valuation of Udayana Green Open Space in Mataram City: A Contingent Valuation Method (CVM) Study - Orchidamoty, Orchidamoty; Diswandi, Diswandi; M Firmansyah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Green Open Space (GOS), as a public good, provides essential ecological, socio-cultural, economic, and aesthetic benefits to the community. However, the economic value associated with these benefits is often not adequately captured or quantified. This study aims to estimate the economic value of Udayana Green Open Space in Mataram City using the Contingent Valuation Method (CVM) within a descriptive quantitative framework. The study population comprises residents of Mataram City across six districts, with the sample size determined using the Slovin formula, resulting in 100 respondents. Primary data were collected through structured questionnaires administered to respondents who met the predefined criteria, while secondary data were compiled using an empirical approach due to the limited availability of official data from relevant institutions. The data were analyzed using multiple linear regression. The results indicate that the mean willingness to pay (WTP) is IDR 2,000, with an estimated total annual economic value of approximately IDR 1.5 billion. Furthermore, the findings reveal that, simultaneously, education, income, visitation frequency, GOS facilities, environmental awareness, and institutional factors have a positive and statistically significant effect on respondents’ WTP. However, partial analysis shows that education and environmental awareness do not have a statistically significant effect on WTP.